2022
DOI: 10.1515/znc-2022-0082
|View full text |Cite
|
Sign up to set email alerts
|

Exploring phytochemical constituents ofAchillea arabicaKotschy. ethanolic flower extract by LC-MS/MS and its possible antioxidant and antidiabetic effects in diabetic rats

Abstract: The aim of this study was to reveal the antidiabetic and antioxidant effects of ethanolic lyophilized extract of Achillea arabica flower extract against streptozotosine (STZ)-induced in diabetic rats and to determine its phytochemical content by liquid chromatography with tandem mass spectrometry (LC-MS/MS). After toxicity test, 35 female rats were divided into five groups. Control, diabetes mellitus (DM), A.arabica (400 mg/kg) extract, DM + A. arabica (400 mg/kg) extract and DM + Glibenclamide (2 mg/kg). It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Many studies have reported that phytochemicals can ameliorate obesity-induced diabetes mellitus in vivo and in vitro [ 28 , 29 ]. In this study, we have demonstrated that phycocyanin can protect against high glucose high fat diet induced diabetes mellitus in mice and can also ameliorate the insulin-resistant effect of SMMC-7721 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that phytochemicals can ameliorate obesity-induced diabetes mellitus in vivo and in vitro [ 28 , 29 ]. In this study, we have demonstrated that phycocyanin can protect against high glucose high fat diet induced diabetes mellitus in mice and can also ameliorate the insulin-resistant effect of SMMC-7721 cells.…”
Section: Discussionmentioning
confidence: 99%
“…CGA lowers the absorption of glucose in the stomach by inhibiting G‐6‐phosphate translocase and sodium‐glucose cotransporter (Meng et al., 2013 ). The presence of major compounds, such as quinic acid, cyranoside, CGA, and cosmosiin in the Achillea arabica flower extract, lyophilized in ethanol showed significant antioxidant effects in streptozotocin‐induced diabetic rats, reducing blood glucose, serum glucose, HbA1c, liver, and kidney damage biomarkers (Hanalp et al., 2023 ). A research article by Kato et al.…”
Section: Promising Dietary Phenolic Compoundsmentioning
confidence: 99%